The Integration of Pancasila and Islamic Law in Indonesia: Community Practices in Aceh and West Sumatra - Hamdi, Syaibatul; Andhika, M. Rezki; Rahimi, Rahimi; Ikhwan, M (Hukum Keluarga Islam IAIN LANGSA, 2023)
This study examines the relationship between Pancasila, Indonesia's foundational ideology, and Islamic Law, focusing on its implementation in Aceh and West Sumatra. Specifically, the research explores how communities perceive, interpret, and integrate Pancasila within the framework of Islamic Law in both legal practices and policy implementation. Employing a qualitative research methodology, data were collected through in-depth interviews with 10 informants, including religious scholars, government officials, and community leaders, as well as observations and document analysis. The data were analyzed using thematic analysis to identify key patterns and challenges in the integration process. The findings reveal that while the implementation of Islamic Law in Aceh follows a formalized legal framework with Sharia-based regulations, in West Sumatra, Islamic values are embedded within customary law under the principle of Adat Basandi Syarak, Syarak Basandi Kitabullah. Despite differences in implementation, both regions demonstrate that Pancasila and Islamic Law are perceived as complementary rather than contradictory. However, challenges remain, including tensions in law enforcement, concerns about human rights, and the need for policy adjustments to balance religious aspirations with national integration. This study contributes to the discourse on legal pluralism in Indonesia by providing empirical insights into how Islamic Law operates within the Pancasila framework, offering a nuanced perspective on the dynamics between religion, state ideology, and governance in a pluralistic society.